Bibliometric analysis of SCAMPER strategy over the past 20 years - Yusinta Dwi Ariyani; Insih Wilujeng; Siti Irene Astuti Dwiningrum (Institute of Advanced Engineering and Science, 2022)
This study aimed to explore the publication trends of substitute, combine, adapt, modify, put to another use, eliminate, and rearrange (SCAMPER) research over the past 20 years. The method used to explore the research trends was literature review through bibliometric analysis. The results of the bibliometric analysis identify core research or authors, as well as their relationship, by covering all the publications related to a given topic or field. The publication related to SCAMPER from 2000 to 2020 was retrieved from Google Scholar, Pubmed, and Scopus. The research trends of SCAMPER were visualized using the VOSviewer program. The results showed that the research trend of SCAMPER has continually increased over the past 20 years, especially in the last five years. A network analysis based on the co-occurrence of keywords showed the main keyword study was creative thinking. Based on the analysis of the field of study, SCAMPER has been widely studied in science. Only a few have been studied in engineering, architecture, sports, social studies, management, mathematics, psychology, and health. The benefit of this research can illustrate the extent to which SCAMPER strategies have been applied to develop 21st-century skills.